Removal of metals from water of Yarinacocha Lagoon with activated carbon from cocoa pod husks - Ronald M. Lozano-Reátegui; Vitelio Asencios-Tarazona; Fernando P. Taboada-Gutiérrez; Iris O. Ruiz-Yance; Manuel R. Guerrero-Ochoa; Weninger Pinedo-Chambi; Mariano M. Mendoza-Carlos (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The problem addressed is the contamination of the Yarinacocha Lagoon water by heavy metals and poor use of agricultural residues. It was manufactured activated carbon from cocoa (Theobroma cacao L.) pod husks and determined its adsorbent effect in removing polluting metals from the waters of the Yarinacocha Lagoon. The response surface methodology was applied with factorial designs 33 and 32, with three replicates to optimize obtaining the adsorbent and measure its effectiveness in metal removal. The modeling of the pyrolysis process resulted in 17.27 g of activated carbon from 295.72 g of dry pod husks, optimal with the following optimal parameters: 150 °C as activation temperature, 450 °C as carbonization temperature, and 2.5 hours as modification time. This resulted in effective removal of pollutant metals (aluminum: 91.43%, copper: 75%, iron: 58.33% and zinc: 58.33%), from waters samples demonstrating that it is possible to manufacture activated carbon from cocoa pod husks, with an adsorbent potential to remove metals from the waters of the Yarinacocha Lagoon.